“Keeping the ball rolling”: Addressing the enablers of, and barriers to, sustainable lifestyles - Axon, Stephen (Journal of Environmental Psychology, 2017)
The impetus for addressing climate change is real and present, but its translation into action lacks immediacy and severity, and involves reorientating our lifestyles and economies towards sustainability. Drawing on focus groups conducted in seven UK communities, specific interventions were identified as encouraging change in the short-term, maintaining momentum in the medium-term and sustaining sustainability in the long-term to address various enablers of, and barriers to, sustainable lifestyles. The findings illustrate that there are multiple entry points and influencing periods for sustainable living. Given the importance of the temporal dimension in encouraging and sustaining practices for sustainable lifestyles, the paper advances a “what works” approach to sustainable lifestyles that can be embedded with practical solutions. This approach creates a synergy between what individuals want to do to live sustainably and how they want to do this with interventions that are known to create meaningful lifestyles changes and maintain sustainable living.
Keywords: Addressing climate change; Barriers; Enablers; Interventions; Social practices; Sustainable lifestyles; dept.egm

Stakeholder engagement in coastal sustainability transitions: an emerging research agenda - Axon, Stephen; Chapman, Anya; Light, Duncan (Regions Magazine, 2017)
Keywords: dept.egm

Coastal sustainability ii: frontiers for regional transition towards sustainability transitions in the coastal zone - Morrissey, John E.; Heidkamp, Patrick (Regions Magazine, 2017)
Keywords: dept.egm

Land-use change at temporary group-housing sites in post-Katrina Louisiana - Zavar, Elyse; Hagelman, III, Ronald; Lavy, Brendan; Prince, Benjamin (Natural Hazards Review, 2017)
To shelter the large number of displaced households following Hurricane Katrina (2005), FEMA, in conjunction with local governments, established 110 temporary group-housing sites throughout impacted Louisiana. The purpose of this study is to identify how temporary group-housing sites influenced the land use of post-Katrina Louisiana. Using aerial imagery, this study assessed the land use of each temporary group-housing site prior to Hurricane Katrina in 2005 and again in 2010. Of the 110 group-housing sites, 54.5% reverted to the previous land use, 29.1% returned to the previous land use with improvements, and 16.3% of the sites changed land use. Using census data from 2000 and 2010, site characteristics, and property records, this study employed a multinomial logistic regression to identify statistically significant variables in predicting land-use change in post-Katrina Louisiana. The results indicate that, especially in neighborhoods with high demand for land, FEMA temporary group-housing sites tended to be redeveloped into new land uses.
Keywords: Aerial imagery; Aerial photography; Group housing; Housing; Hurricane Katrina; Hurricane Katrina 2005; Hurricane katrina; Hurricanes; Land use; Land-use change; Local government; Louisiana; Multinomial logistic regression; Population statistics; Significant variables; Site characteristics; Temporary group housing; United States; aerial photograph; census; dept.egm; hazard assessment; hazard management; housing project; land use change; local government; neighborhood

Geospatial sculpture: Nonverbal communication through the tactilization of geospatial data - Heidkamp, C. Patrick; Slomba, Jeffrey T. (GeoHumanities, 2017)
Keywords: 3D visualization; Connecticut; Escultura Geoespacial; GeoSpatial Sculpture; dept.art; dept.egm; geografías no verbales; nonverbal geographies; peer-reviewed; tactilización; tactilization; visualización en 3D; 三维可视化; 地理空间雕塑; 康涅狄格; 触觉化; 非语言的地理

El género Jaltomata Schltdl. (Solanaceae) en la región La Libertad y un nuevo taxón del Norte de Perú - González, Segundo Leiva; Mione, Thomas; Yacher, Leon (Arnaldoa, 2017)
Keywords: dept.egm

Coastal Sustainability I: Challenges, Methods and Opportunities - Heidkamp, C. Patrick; Morrissey, John E. (Regions Magazine, 2017)
Keywords: dept.egm

Assessing the transition potential of 3D ocean farming in Long Island Sound - Kelly, Erin; Heidkamp, Patrick; Miller, Matthew D. (Regions Magazine, 2017)
Keywords: dept.egm

µUAS: New tools for monitoring coastal resilience - Graves, Scott M (Regions, 2017)
Keywords: dept.egm; ⛔ No DOI found